Nefrotoxicidade por aminoglicosídeos: prevalência; mortalidade e fatores de risco - Oliveira, João Fernando Picollo (2008)
Nephrotoxicity is the main adverse effect of aminoglycoside use. There are few information about its prevalence and risk factor in intensive care unit patients. Objectives: To assess the prevalence, mortality and risk factors for aminoglycoside nephrotoxicity in ICU patients. Casuistic and Method: In order to assess the prevalence of, and risk factors for aminoglycoside nephrotoxicity in the ICU, 360 consecutive patients starting aminoglycoside therapy in the ICU with a baseline calculated GFR (cGFR) ≥30 ml/min/1.73 m2 were evaluated. Results: Of them, 209 (58%) developed aminoglycoside-induced nephrotoxicity (AKI, decrease in cGFR >20% from baseline), while 151 did not (non-AKI). Both groups had similar baseline cGFR. The AKI group developed a lower cGFR nadir (45 ± 27 vs. 79 ± 39 ml/min/1.73 m2, p<0.001), was older (56 ± 18 y vs. 52 ± 19 y, p=0.033), had a higher prevalence of diabetes (19.6% vs. 9.3%, p=0.007), used other nephrotoxic drugs (51% vs. 38%, p=0.024) and iodinated contrast more frequently (18% vs. 8%, p=0.0054), showed higher prevalence of hypotension (63% vs. 44%, p=0.0003), shock (56% vs. 31%, p<0.0001), and jaundice (19% vs. 8%, p=0.0036). Mortality was 44.5% in the AKI and 29.1% in the non-AKI groups (p=0.0031). A logistic regression model identified as significant (p<0.05) independent factors affecting aminoglycoside-induced nephrotoxicity baseline cGFR<60 ml/min/1.73 m2 (OR 0.42), diabetes (OR 2.13), simultaneous use of other nephrotoxins (OR 1.61) or iodinated contrast (OR 2.13), and hypotension (OR 1.83). Conclusion: The AKI was frequent among ICU patients using aminoglycoside, and it was associated with high mortality. The presence of diabetes, hypotension, simultaneous use of other nephrotoxic drugs, and iodinated contrast were independent risk factors for the development of aminoglycoside-induced nephrotoxicity.